2009
DOI: 10.1002/asi.21078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of domain knowledge on reference search with the PubMed database: An experimental study

Abstract: Many researchers in medical and life sciences commonly use the PubMed online search engine (http:// www.pubmed.gov) to access the MEDLINE bibliographic database. The researchers' strategies were investigated as a function of their knowledge of the content area. Sixteen life science researchers with no experience in neuroscience and 16 neuroscience researchers of matched professional experience performed five bibliographic search tasks about neuroscience topics. Objective measures and concomitant verbal protoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 70 publications
(132 reference statements)
0
52
0
Order By: Relevance
“…During this process, however, they may experience conflicts and disagreements in defining curation roles and thus yield contested interpretation of curated data. Previous research indicates that scientists' domain knowledge affects their information seeking behavior and their interactions with information systems and software tools (Brown, 2003;Hemminger et al, 2007;Vibert et al, 2009;Wu et al, 2012). It can be assumed that biologists have a high level of declarative knowledge of biology, whereas computational scientists have a high level of procedural knowledge of computer systems.…”
Section: Domain Knowledge In Genome Curationmentioning
confidence: 99%
“…During this process, however, they may experience conflicts and disagreements in defining curation roles and thus yield contested interpretation of curated data. Previous research indicates that scientists' domain knowledge affects their information seeking behavior and their interactions with information systems and software tools (Brown, 2003;Hemminger et al, 2007;Vibert et al, 2009;Wu et al, 2012). It can be assumed that biologists have a high level of declarative knowledge of biology, whereas computational scientists have a high level of procedural knowledge of computer systems.…”
Section: Domain Knowledge In Genome Curationmentioning
confidence: 99%
“…Although many of the complex queries supported by our search tool could potentially be decomposed into a series of simple keyword searches, studies [66][67][68] have also shown that finding information using keyword search alone is time-consuming and frequently prone to error. A French study [67] has investigated keyword search efficiency in a group of 32 life science researchers who were given various bibliographic search tasks using the PubMed online medical research database. The study sought to investigate the effects of domain knowledge (in this case, neuroscience) and resource knowledge (PubMed) on the speed and accuracy of reference searching.…”
Section: Overviewmentioning
confidence: 99%
“…Although time is included in descriptions of the context of information retrieval [9] and is a commonly used (yet difficult to interpret) measure of search [4], few studies have examined the impact of limited time on search. Differences in searching behavior have been found to be related to a number of contextual and situational factors including perceived task difficulty [15], search expertise [25], domain expertise [27] and system performance [21]; however, the impact of limited time on information search behaviors and outcomes is little understood.…”
Section: Motivationmentioning
confidence: 99%